(4x+3)(3x-5)=(4x-3)(3x+5)

Simple and best practice solution for (4x+3)(3x-5)=(4x-3)(3x+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4x+3)(3x-5)=(4x-3)(3x+5) equation:


Simplifying
(4x + 3)(3x + -5) = (4x + -3)(3x + 5)

Reorder the terms:
(3 + 4x)(3x + -5) = (4x + -3)(3x + 5)

Reorder the terms:
(3 + 4x)(-5 + 3x) = (4x + -3)(3x + 5)

Multiply (3 + 4x) * (-5 + 3x)
(3(-5 + 3x) + 4x * (-5 + 3x)) = (4x + -3)(3x + 5)
((-5 * 3 + 3x * 3) + 4x * (-5 + 3x)) = (4x + -3)(3x + 5)
((-15 + 9x) + 4x * (-5 + 3x)) = (4x + -3)(3x + 5)
(-15 + 9x + (-5 * 4x + 3x * 4x)) = (4x + -3)(3x + 5)
(-15 + 9x + (-20x + 12x2)) = (4x + -3)(3x + 5)

Combine like terms: 9x + -20x = -11x
(-15 + -11x + 12x2) = (4x + -3)(3x + 5)

Reorder the terms:
-15 + -11x + 12x2 = (-3 + 4x)(3x + 5)

Reorder the terms:
-15 + -11x + 12x2 = (-3 + 4x)(5 + 3x)

Multiply (-3 + 4x) * (5 + 3x)
-15 + -11x + 12x2 = (-3(5 + 3x) + 4x * (5 + 3x))
-15 + -11x + 12x2 = ((5 * -3 + 3x * -3) + 4x * (5 + 3x))
-15 + -11x + 12x2 = ((-15 + -9x) + 4x * (5 + 3x))
-15 + -11x + 12x2 = (-15 + -9x + (5 * 4x + 3x * 4x))
-15 + -11x + 12x2 = (-15 + -9x + (20x + 12x2))

Combine like terms: -9x + 20x = 11x
-15 + -11x + 12x2 = (-15 + 11x + 12x2)

Add '15' to each side of the equation.
-15 + -11x + 15 + 12x2 = -15 + 11x + 15 + 12x2

Reorder the terms:
-15 + 15 + -11x + 12x2 = -15 + 11x + 15 + 12x2

Combine like terms: -15 + 15 = 0
0 + -11x + 12x2 = -15 + 11x + 15 + 12x2
-11x + 12x2 = -15 + 11x + 15 + 12x2

Reorder the terms:
-11x + 12x2 = -15 + 15 + 11x + 12x2

Combine like terms: -15 + 15 = 0
-11x + 12x2 = 0 + 11x + 12x2
-11x + 12x2 = 11x + 12x2

Add '-12x2' to each side of the equation.
-11x + 12x2 + -12x2 = 11x + 12x2 + -12x2

Combine like terms: 12x2 + -12x2 = 0
-11x + 0 = 11x + 12x2 + -12x2
-11x = 11x + 12x2 + -12x2

Combine like terms: 12x2 + -12x2 = 0
-11x = 11x + 0
-11x = 11x

Solving
-11x = 11x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-11x' to each side of the equation.
-11x + -11x = 11x + -11x

Combine like terms: -11x + -11x = -22x
-22x = 11x + -11x

Combine like terms: 11x + -11x = 0
-22x = 0

Divide each side by '-22'.
x = 0

Simplifying
x = 0

See similar equations:

| 12x+50=7x-40 | | 5x-5=5(x+7) | | 6+13=6+(n+5) | | .12222= | | 5c+c=78 | | -5x+13=14 | | -2=20x | | 6n^2-18n-168=0 | | 12m-15=-3 | | 3x-0.4=1.4 | | Y+28=x+5 | | 8(x+3)-3x=2(x+12)+3x | | B+ax=2x | | -7v-19=6(1+3v) | | -5(x+3)+8=-7 | | 36w=648 | | 0.4(-5)+6.1= | | 6u^2+u-6=0 | | -2(t-2)+7t=9T-3 | | 3x+7+6x=106 | | -3(y-2)=-2y-1 | | ln(x+1)+ln(3)=ln(2x) | | x-15=4y | | 5.25n=46.50 | | 5*(12-3)=5*e | | 15n=5.25 | | 6a+3+2a=19 | | 8y-16=8y+-16 | | 8=2(4j+1)-5j | | 5(6x+2)-8=30x+2 | | 5(y+9)=-2y-4 | | b=75 |

Equations solver categories